Interpretation of Human Thought using EEG Signals and LabVIEW - Norizam, Sulaiman; Cheng, Chee Hau; Amran, Abdul Hadi; Mahfuzah, Mustafa; M. S., Jadin (2014)
This document describes the analysis of Electroenchaplogram (EEG) or brain signals using computational tool (LabVIEW) to interpret human thought such as moving forward, backward, turn right, turn left and to stop. This study is conducted to assist the disable people to communicate with external environment. The EEG signals are captured using wireless EEG amplifier while the subject in relax conditioin. Then, the signals are analyzed in LabVIEW to reveal the features to describe human thought. The features will be applied by the state machine to control the movements. The extracted EEG features are the ratio of EEG power spectrum from 14 channels. The Read Biosignal and STFT Spectrogram Toolbox of LabVIEW are used to process the EEG raw data and to produce the EEG Power Spectrum. Then, the pattern of the EEG Power Spectrum are studied to provide the feature vectors for the state machine. The outcome of the study indicates that the movement or direction can be determined based on the extracted features of EEG signals in LabVIEW.